Poroid adnexal skin tumors with YAP1 fusions exhibit similar histopathologic features: A series of six YAP1‐rearranged adnexal skin tumors. (21st March 2021) - Prieto‐Granada, Carlos; Morlote, Diana; Pavlidakey, Peter; Rodriguez‐Waitkus, Paul; Ramirez, Cristina; Florento, Elena; Swensen, Jeffrey; Gatalica, Zoran; Stevens, Todd M.
Abstract: Background: Adnexal skin tumors are diagnostically challenging with few known molecular signatures. Recently, however, YAP1‐MAML2 and YAP1‐NUTM1 fusions were identified in poroid adnexal skin tumors. Methods: Herein, we subjected eight poroid adnexal skin tumors (three poromas and five porocarcinomas) to fusion gene analysis by whole transcriptome sequencing and next‐generation DNA sequencing analysis. Results: YAP1 fusions were identified in six cases. YAP1‐NUTM1 fusions were identified in two poromas and three porocarcinomas. A single case of porocarcinoma harbored a YAP1‐MAML2 fusion. Two cases were negative for gene fusion. All cases that harbored YAP1‐NUTM1 fusions showed nuclear protein in testis (NUT) expression by immunohistochemistry, with NUT being negative in the YAP1‐MAML2 ‐positive case. In this case series, we provide a detailed histopathologic description of six YAP1 ‐fused poroid skin tumors, which we show harbor reproducible histopathologic features, to include broad, bulbous tumor tongues with admixtures of basaloid, poroid cells punctuated by squamatized cuticles and ductules, with uniform tumor nuclei featuring frequent grooves and pseudonuclear inclusions. Conclusions: Awareness of the characteristic histopathologic features of YAP1 ‐fused poroid adnexal skin tumor is a step toward a more reproducible classification of adnexal skin tumors as well as a step toward targeted therapy for metastatic and/or unresectable examples of this poroid group of neoplasms.